2009
DOI: 10.3758/app.71.3.594
|View full text |Cite
|
Sign up to set email alerts
|

Processing of natural images is feedforward: A simple behavioral test

Abstract: Natural images can be classified so rapidly that it has been suggested that their analysis is based on a first single pass of processing activity through the visuomotor system. We tested this theory in a visuomotor priming task in which speeded pointing responses were performed toward one of two target images containing a prespecified stimulus (e.g., animal vs. nonanimal, ellipse vs. rectangle). Target pictures were preceded by prime pictures of the same or an opposite category, linked to either the same or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 45 publications
9
43
0
Order By: Relevance
“…The duration and spatial extent of such a detour into the wrong quadrant increased with prime-target SOA. These basic results are in line with previous findings (Schmidt, 2002;Schmidt & Schmidt, 2009;Schmidt & Seydell, 2008).…”
Section: Methodssupporting
confidence: 83%
See 3 more Smart Citations
“…The duration and spatial extent of such a detour into the wrong quadrant increased with prime-target SOA. These basic results are in line with previous findings (Schmidt, 2002;Schmidt & Schmidt, 2009;Schmidt & Seydell, 2008).…”
Section: Methodssupporting
confidence: 83%
“…This enhancement takes place before the occurrence of prime and target stimuli and is an integral part of the feedforward processes they elicit, without necessarily affecting the recurrent processes that lead to visual awareness. This way, feature-based attention can modulate the dynamics indicate that the earliest phases of the priming effect depend only on prime but not on target characteristics, and that they are independent of visual awareness of the prime (Mattler, 2003;Schmidt & Schmidt, 2009;Vath & Schmidt, 2007;Vorberg et al, 2003). The rapid-chase theory of response priming Schmidt & Schmidt, 2009;Vath & Schmidt, 2007) therefore proposes that response priming is based on sequential, nonoverlapping waves of rapid feedforward activation ( feedforward sweeps; see Lamme & Roelfsema, 2000; see also Bullier, 2001;Thorpe, Fize, & Marlot, 1996;VanRullen & Thorpe, 2002), which are elicited in turn by primes and targets and traverse the visuomotor system in strict sequence, directly triggering the assigned responses (Neumann, 1990).…”
Section: General R R Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In several studies, Schmidt and Schmidt (2009) and Schmidt, Niehaus, and Nagel (2006) investigated the effects of unconsciously (or preconsciously) processed information on pointing movements: They found that the initial trajectory of a pointing movement is guided by feedforward-processed visual information. Interestingly, both the results obtained by Schmidt and coworkers, and the results we obtained in Experiment 3 share one critical feature: Both prosaccades and pointing movements do not require a spatial transformation or remapping of a response, and are completely stimulus-driven.…”
Section: Discussionmentioning
confidence: 99%